Cancer patients' acceptability of incorporating an epidemiology questionnaire within a clinical trial. (June 2015) - Cuffe, Sinead; Hon, Henrique; Tobros, Kimberly; Espin-Garcia, Osvaldo; Brhane, Yonathan; Harland, Luke; Fadhel, Ehab; Eng, Lawson; LaDelfa, Anthony; Waldron, John; Siu, Lillian L; Chen, Bingshu E; et al.
Background/aims: Understanding the influence or impact of epidemiological factors on cancer outcomes in clinical trials can broaden our knowledge of disease, trial populations and therapeutic effects thus leading to improved patient care. However, there is a lack of data on cancer patients' compliance with an epidemiology questionnaire in the context of a clinical trial. Patients and methods: Cancer patients were provided with a hypothetical scenario and surveyed regarding their willingness and preferences to complete an epidemiology questionnaire if incorporated into a cancer therapy trial. Patient compliance with completing a voluntary epidemiology questionnaire and trial coordinators perceptions therein were separately determined in the NCIC Clinical Trials Group HN.6 clinical trial, an ongoing randomized phase III trial comparing two first-line treatment regimens in patients with locoregionally advanced head and neck cancer. Results: Of 617 cancer patients from community, academic and tertiary cancer centres, the majority were willing to complete an epidemiology questionnaire either unconditionally (45%), or provided it did not inconvenience them (31%); 4% would refuse. Patients preferred shorter questionnaires of 30–50 questions requiring 10–20 min to complete, administered over 1–3 sessions. Patients were less willing, but still compliant, to answer questions relating to sexual history (71%) and annual household income (66%) relative to other questions (>90%). Eighteen percent thought that the questionnaire should be mandatory, with 31% believing that they may benefit personally from such research. In the HN.6 trial, compliance averaged 94.8% per question. Conclusions: Cancer patients are very willing to complete epidemiology questions in clinical trials.